A mathematical model of verification strategies. Issue 6 (22nd August 2018) - Salado, Alejandro; Kannan, Hanumanthrao
Abstract: The field of systems engineering has recently experienced a new push for unveiling its scientific foundations and using them to inform better practice. The majority of the research effort towards a theory of systems engineering has concentrated on the early phases of the system's lifecycle, especially in the areas of problem formulation and system architecture and design. However, and despite their importance for system success, the design of verification strategies has received little attention. Current work is of procedural nature, providing guidance instead of enabling computation, or is specific to a particular verification case. As a result, the definition of verification strategies in practice continues to be driven by heuristics and best practices. This has shown to be suboptimal. In order to fill in this gap, this paper contributes to the theory of systems engineering with a mathematical model of verification strategies. The mathematical model is generic, capturing verification comprehensively, and enables computation. First, a descriptive case is presented to facilitate understanding how the mathematical model relates to practice. Second, a quantitative case is presented to justify the need of the model.